New Financial Alternatives in Seeding Entrepreneurship: Microfinance, Crowdfunding, and Peer‐to‐Peer Innovations. (3rd December 2014) - Bruton, Garry; Khavul, Susanna; Siegel, Donald; Wright, Mike
<x xml:space="preserve">Abstract</x> New financing alternatives, such as microfinance, crowdfunding, and peer‐to‐peer lending, have expanded rapidly. To date, few studies have investigated the antecedents and consequences of these financing mechanisms. This special issue provides an academic foundation for understanding new financial options that entrepreneurs can now use to start and grow ventures. In the introductory article, we integrate strands of the literature on emerging innovations in entrepreneurial finance and provide a framework for a systematic approach to new research questions. We conclude with a discussion of the six papers in the special issue and demonstrate how they contribute to the framework.